KEY STAGES IN THE FORMATION AND DEVELOPMENT OF INTERNATIONAL COOPERATION ON DIGITAL TRADE (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The development of international cooperation on digital trade has progressed significantly over the past few decades, largely driven by the digitalization of global commerce and the growth of e-commerce. This paper analyzes the key stages in the formation and development of digital trade cooperation among states, particularly focusing on multilateral and bilateral agreements, treaties, and frameworks such as the World Trade Organization (WTO) and regional trade blocs. It examines the legal structures, challenges, and successes of interstate cooperation on digital trade, shedding light on how digital trade regulation is shaping the future of global commerce. This analysis highlights the importance of international collaboration in regulating cross-border data flows, e-commerce, and technology transfer.